CRIMINOLOGICAL REVIEW OF DEVIANT HOMOSEXUAL BEHAVIOR OF PRISONERS IN CLASS I MADIUN PRISON INSTITUTION - Wiranata, Herning Widya; Jarodi, Odi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article discusses the world of corrections as a place of punishment for prisoners, which still causes dynamics of internal problems that have not been resolved. The clash with the limitations imposed by the state on the basic needs of prisoners gives rise to various social problems as a result of the social interaction process that can disrupt the process of the correctional system. The problem of deviant sexual behavior by prisoners as a result of the loss of the right to sexual relations is something that has so far become an unresolved discourse. The purpose of this research is to identify the adaptation patterns of homosexual prisoners in prison, which mapping can later become material for strategies to control the problem. This article uses a descriptive qualitative research method to examine dynamic field phenomena. Data collection techniques were carried out through interviews and document studies. The results of the discussion show that homosexuals have a pattern of conformity and innovation adaptation that can be observed and studied as material for controlling sexual deviation problems in prisons using situational crime prevention. Keywords: Correctional; Homosexual; Prisoners